LiMnO2-coated P '2-phase transition metal oxide manganese-based positive electrode material and preparation method thereof

By wet coating LiMnO2 on the surface of the SIBs positive electrode material, the problem of easy water absorption and poor electrochemical stability of the material is solved, and higher capacity retention and cycling stability are achieved.

CN119503886APending Publication Date: 2025-02-25NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411754797.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

There are gaps in capacity and lifetime of existing SIBs cathode materials, and they are prone to water absorption, resulting in poor electrochemical stability.

Method used

LiMnO2 is coated on the surface of the P’2 phase transition metal oxide manganese-based positive electrode material by wet method to isolate the direct contact between the material and the electrolyte and the moisture in the air, thereby improving the electrochemical stability of the material.

Benefits of technology

It effectively improves the capacity retention rate and cycle stability of the material, extends the service life of the material, and improves the rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503886A_ABST
    Figure CN119503886A_ABST
Patent Text Reader

Abstract

The invention discloses a LiMnO2 coated P '2 phase transition metal oxide manganese-based positive electrode material and a preparation method thereof. The method comprises the following steps: uniformly mixing Na2CO3, Mn2O3 and TiO2 according to a molar ratio of 4.375: 5.25: 1, and carrying out ball milling for 5-8 hours to obtain a precursor; the precursor is subjected to solid-phase sintering, sintering is carried out for 15 hours at the temperature of 1000-1050 DEG C, furnace cooling is carried out, and the P '2-phase transition metal oxide manganese-based positive electrode material Na < 0.7 > Ti < 0.16 > Mn < 0.84 > O < 2 > is obtained through one-time sintering. The preparation method comprises the following steps: uniformly mixing Li2CO3 and Na0. 7Ti0. 16Mn0. 84O2 according to a mass ratio of 2-4%, adding ethanol, stirring for 5-6 hours, drying, and carrying out high-temperature solid-phase sintering at 300-400 DEG C to obtain the LiMnO2 coated P '2-phase transition metal oxide manganese-based positive electrode material. On the basis of not destroying the original phase structure of the material, a protective layer with the thickness of several nanometers is deposited on the surface of the material, so that the water absorption property of the material is improved while the ion transmission capability is improved, the potential window of the material is widened, and the rate capability and the cycling stability of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium battery positive electrode material preparation, and relates to a LiMnO2-coated P'2 phase transition metal oxide manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] As the driving force of social development, the main source of energy is still non-renewable fossil energy. However, excessive exploitation and use of fossil energy will cause a series of environmental problems such as damage to the geological environment and greenhouse effect. At present, clean energy power generation has been promoted on a large scale, which has greatly alleviated my country's power pressure and enriched the country's energy reserves. However, clean energy power generation is easily affected by climate and geographical location, and the electricity it generates needs to be stored in large energy storage equipment before it can be connected to the power grid. In recent years, the demand for large-scale energy storage equipment has increased year by year, but there is a lack of low-cost and sustainable secondary energy storage batteries that can be applied to this field for a long time. Although lithium-ion batteries have excellent performance, the scarcity of lithium resources and their uneven distribution on the earth will cause the cost of lithium-ion batteries to rise year by year. Therefore, in the long run, it is crucial to develop low-cost, high-safety and sustainable large-scale energy storage devices and the application of lithium-ion batteries in the field of portable energy storage to form a complementary pattern of advantages. The reserves of sodium in the earth's crust (2.36wt%) are much higher than those of lithium (0.0017wt%). At the same time, the price of commonly used sodium salts is much lower than that of lithium salts, which makes SIBs lower in cost and more promising.

[0003] Sodium resources are abundant and evenly distributed, so SIBs have great potential in large-scale energy storage applications. At present, there is still a gap between the capacity and life of SIBs cathode materials and anode materials. Therefore, the development of high-performance cathode materials is the key to promoting the commercialization of SIBs. Layered TM oxides in cathode materials have attracted widespread attention due to their easy synthesis, high volume energy density, and similar charging and discharging principles to traditional lithium-ion battery layered cathode materials. According to the coordination environment of Na+ and the number of oxygen layers in different stacking orders, layered cathode materials are usually divided into P2 and O3. The traditional P2 phase belongs to the P63 / mmc space group and the hexagonal system. Its orthorhombic allotrope, namely the P'2 phase, is a material with lattice distortion formed by the Jahn-Teller distortion effect of high-spin TM cations. The high-temperature rapid cooling synthesis conditions make P'2-NaxTMO2 free of TM vacancy defects and have a higher specific capacity. However, since the P'2 material easily absorbs water, it needs to be coated on the surface of the material to give the material better rate performance and cycle performance.

[0004] The wet chemical coating method can form a uniform and dense coating layer on the surface of the positive electrode material, effectively isolating the direct contact between the positive electrode material and the electrolyte, reducing side reactions, blocking the contact with moisture in the air, and improving the electrochemical stability of the material, which has excellent development prospects. Summary of the invention

[0005] The purpose of the present invention is to provide a LiMnO2 coated P'2 phase transition metal oxide manganese-based positive electrode material and a preparation method thereof. The method coats LiMnO2 on the surface of the P'2 positive electrode material by a wet method, isolates the positive electrode material from direct contact with electrolyte and moisture in the air, and improves the capacity retention rate of the material.

[0006] The technical solution for achieving the purpose of the present invention is as follows:

[0007] The preparation method of LiMnO2 coated P'2 phase transition metal oxide manganese-based positive electrode material comprises the following steps:

[0008] Step 1, according to the molar ratio of Na2CO3, Mn2O3 and TiO2 being 4.375:5.25:1, the three materials are uniformly mixed and ball-milled for 5 to 8 hours to obtain a precursor; the precursor is then solid-phase sintered at 1000 to 1050°C for 15 hours and cooled in the furnace to obtain a P'2 phase transition metal oxide manganese-based positive electrode material Na 0.7 Ti 0.16 Mn 0.84 O2;

[0009] Step 2: Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 O2 is uniformly mixed in a mass ratio of 2-4%, ethanol is added and stirred for 5-6 hours, and after drying, high-temperature solid-phase sintering is performed at 300-400° C. to obtain a LiMnO2-coated P'2 phase transition metal oxide manganese-based positive electrode material.

[0010] Preferably, in step 1, the ball milling speed is 400 r / min and the time is 6 to 7 h.

[0011] Preferably, in step 1, the heating time of the solid phase sintering is 196 to 206 minutes.

[0012] Preferably, in step 1, the sintering temperature of the solid phase sintering is 1000-1050° C., and the sintering holding time is 15-16 hours.

[0013] Preferably, in step 2, the Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 The O2 mixing mass ratio is 2.5-3.5%.

[0014] Preferably, in step 2, the stirring time for adding ethanol is 5 to 6 hours.

[0015] Preferably, in step 2, the drying time is 8 to 9 hours.

[0016] Preferably, in step 2, the high-temperature solid-phase sintering temperature is 350-400° C., and the sintering holding time is 5-6 hours.

[0017] The present invention also provides a LiMnO2-coated P'2 phase transition metal oxide manganese-based positive electrode material prepared by the above preparation method.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] The present invention deposits a protective layer of several nanometers thick on the surface of the material without destroying the original phase structure of the material, thereby improving the ion transmission capacity and the water absorption of the material, thereby widening the potential window of the material and thus improving the rate performance and cycle stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD spectrum of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 2.

[0021] Figure 2 This is a SEM image of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 2.

[0022] Figure 3 This is the EDS element distribution diagram of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 2.

[0023] Figure 4 , 5 This is a TEM image of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 2.

[0024] Figure 6 These are the first and tenth cycle charge-discharge curves of the P'2 phase manganese-based positive electrode material coated with LiMnO2 prepared in Comparative Example 1 at 0.1C.

[0025] Figure 7 These are the first and tenth cycle charge-discharge curves of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 2 at 0.1C.

[0026] Figure 8 This is a rate performance diagram of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 1 and Comparative Example 2.

[0027] Fig. 9 It is a cycle performance diagram of the LiMnO2-coated P'2 phase manganese-based positive electrode material prepared in Example 1 and Comparative Example 2.

[0028] Figures 4 to 9 All the tests were conducted in button cells using the material as the positive electrode, and the test instrument was a Coster electrochemical workstation. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with embodiments and drawings.

[0030] Example 1

[0031] According to the molar ratio of Na2CO3, Mn2O3 and TiO2 of 4.375:5.25:1, the three materials were uniformly mixed and ball-milled for 6 hours to obtain a precursor; the precursor was then solid-phase sintered at 1000°C for 15 hours and cooled in the furnace to obtain the P'2 phase material Na 0.7 Ti 0.16 Mn 0.84 O2. Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 O2 was uniformly mixed at a mass ratio of 2.5%, ethanol was added and stirred for 5 hours, and then high-temperature solid-phase sintering was performed at 350°C after drying to obtain LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 The cycling performance of the prepared material is shown as follows: after 100 cycles at a current density of 1C, the capacity decays by 15.23%.

[0032] Example 2

[0033] According to the molar ratio of Na2CO3, Mn2O3 and TiO2 of 4.375:5.25:1, the three materials were uniformly mixed and ball-milled for 6 hours to obtain a precursor; the precursor was then solid-phase sintered at 1000°C for 15 hours and cooled in the furnace to obtain the P'2 phase material Na 0.7 Ti 0.16 Mn 0.84 O2. Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 O2 was uniformly mixed at a mass ratio of 3%, ethanol was added and stirred for 5 hours, and then high-temperature solid-phase sintering was performed at 350°C after drying to obtain LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84The cycling performance of the prepared material is shown as follows: after 100 cycles at a current density of 1C, the capacity decays by 5.18%.

[0034] Example 3

[0035] According to the molar ratio of Na2CO3, Mn2O3 and TiO2 of 4.375:5.25:1, the three materials were uniformly mixed and ball-milled for 6 hours to obtain a precursor; the precursor was then solid-phase sintered at 1000°C for 15 hours and cooled in the furnace to obtain the P'2 phase material Na 0.7 Ti 0.16 Mn 0.84 O2. Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 O2 was uniformly mixed at a mass ratio of 3.5%, ethanol was added and stirred for 5 hours, and then high-temperature solid-phase sintering was performed at 350°C after drying to obtain LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 The cycling performance of the prepared material is shown as follows: after 100 cycles at a current density of 1C, the capacity decays by 20.25%.

[0036] Example 4

[0037] According to the molar ratio of Na2CO3, Mn2O3 and TiO2 of 4.375:5.25:1, the three materials were uniformly mixed and ball-milled for 6 hours to obtain a precursor; the precursor was then solid-phase sintered at 1050°C for 15 hours and cooled in the furnace to obtain the P'2 phase material Na 0.7 Ti 0.16 Mn 0.84 O2. Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 O2 was uniformly mixed at a mass ratio of 3%, ethanol was added and stirred for 5 hours, and then high-temperature solid-phase sintering was performed at 350°C after drying to obtain LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 The cycling performance of the prepared material is shown as follows: after 100 cycles at a current density of 1C, the capacity decays by 17.35%.

[0038] Example 5

[0039] According to the molar ratio of Na2CO3, Mn2O3 and TiO2 of 4.375:5.25:1, the three materials were uniformly mixed and ball-milled for 6 hours to obtain a precursor; the precursor was then solid-phase sintered at 1000°C for 15 hours and cooled in the furnace to obtain the P'2 phase material Na 0.7 Ti 0.16 Mn 0.84 O2. Li2CO3 and Na 0.7 Ti 0.1 6Mn 0.84 O2 was uniformly mixed at a mass ratio of 3%, ethanol was added and stirred for 5 hours, and then high-temperature solid-phase sintering was performed at 400°C after drying to obtain LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 The cycling performance of the prepared material is shown as follows: after 100 cycles at a current density of 1C, the capacity decays by 19.69%.

[0040] like Figure 1 As shown, the Na2O2 coated with LiMnO2 having a plate-like morphology prepared by the preparation method of the present invention 0.7 Ti 0.16 Mn 0.84 The XRD spectrum of O2 is completely consistent with the standard card PDF#00~027~0752 in the database, indicating that the product is a pure P'2 phase. In addition, the X-ray diffraction peak is sharp and has a high peak intensity, indicating that the crystal form is well developed.

[0041] like Figure 2 As shown, the LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 From the SEM image of O2, it can be seen that the material is plate-shaped and the surface of the material particles has a fine grain structure formed by rapid cooling.

[0042] like Figure 3 As shown, the LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 O2, it can be seen from the EDS elementalmappings that the material elements are evenly distributed, but since EDS cannot detect the Li element, TEM was used to observe the coating layer.

[0043] like Figure 4 , 5 As shown, the LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84It can be seen from the TEM image of O2 that there is a dense coating layer on the surface of the material, and the grain size of the formed coating layer is 0.243nm, which is much smaller than the 0.581nm of the original material.

[0044] like Figure 6 As shown, the LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 From the charge and discharge curve of O2, it can be seen that the material's first-week charging capacity is 117.14 mAh / g, the discharge capacity is 165.95 mAh / g, and the first-week efficiency is 70.58%.

[0045] like Figure 7 As shown, the LiMnO2-coated Na 0.7 Ti 0.16 Mn 0.84 From the charge and discharge curve of O2, it can be seen that the material's first-week charging capacity is 139.48 mAh / g, the discharge capacity is 196.13 mAh / g, and the first-week efficiency is 71.12%.

[0046] like Figure 8 As shown, from the rate performance comparison diagram of Example 1 and Example 2 prepared by the present invention, it can be seen that the rate performance of the material in Example 2 is significantly better than that of the material in Example 1.

[0047] like Fig. 9 As shown, from the cycle performance comparison chart of Example 1 and Example 2 prepared by the present invention, it can be seen that the capacity retention rate of the Example 1 material after 100 charge and discharge cycles is 84.75%, and the capacity retention rate of the Example 2 material after 100 charge and discharge cycles is 94.82%.

Claims

1. Preparation method of LiMnO2 coated P'2 phase transition metal oxide manganese-based positive electrode material, It is characterized in that The following steps are involved: Step 1, according to the molar ratio of Na2CO3, Mn2O3 and TiO2 being 4.375:5.25:1, the three materials are uniformly mixed and ball-milled for 5 to 8 hours to obtain a precursor; the precursor is then solid-phase sintered at 1000 to 1050°C for 15 hours and cooled in the furnace to obtain a P'2 phase transition metal oxide manganese-based positive electrode material Na 0.7 Ti 0.16 Mn 0.84 O2; Step 2: Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 O2 is uniformly mixed in a mass ratio of 2-4%, ethanol is added and stirred for 5-6 hours, and after drying, high-temperature solid-phase sintering is performed at 300-400° C. to obtain a LiMnO2-coated P'2 phase transition metal oxide manganese-based positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of Na2CO3, Mn2O3 and TiO2 is 4.375:5.25:

1.

3. The preparation method according to claim 1, characterized in that: In step 1, the ball milling speed is 400 r / min and the time is 5 to 8 hours.

4. The preparation method according to claim 1, characterized in that: In step 1, the solid phase sintering heating rate is 5°C / min, and the heating time is 186 to 206 min.

5. The preparation method according to claim 1, characterized in that: In step 1, the solid phase sintering is carried out in a muffle furnace, the sintering temperature is 950-1050° C., and the sintering holding time is 15-20 hours.

6. The preparation method according to claim 1, characterized in that: In step 2, the Li2CO3 and Na 0.7 Ti 0.16 Mn 0.84 The O2 mixing mass ratio is 2 to 4%.

7. The preparation method according to claim 1, characterized in that: In step 2, the stirring instrument for adding ethanol is a magnetic stirrer, and the stirring time is 4 to 7 hours.

8. The preparation method according to claim 1, characterized in that: In step 2, the drying is carried out in a blast dryer for 7 to 9 hours.

9. The preparation method according to claim 1, characterized in that: In step 2, the high-temperature solid-phase sintering is carried out in a muffle furnace, the sintering temperature is 300-400° C., and the sintering holding time is 4-7 hours. 10 . The LiMnO 2 -coated P′ 2 phase transition metal oxide manganese-based positive electrode material prepared according to the preparation method of any one of claims 1 to 9 .

11. Use of the LiMnO2 coated P'2 phase transition metal oxide manganese-based positive electrode material according to claim 10 in the preparation of positive electrode materials.